2021
DOI: 10.1525/elementa.2020.00136
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric oil and natural gas hydrocarbon trends in the Northern Colorado Front Range are notably smaller than inventory emissions reductions

Abstract: From 2008 to mid-2016, there was more than a 7-fold increase in oil production and nearly a tripling of natural gas production in the Colorado Denver–Julesburg Basin (DJB). This study utilized air samples collected at the Boulder Atmospheric Observatory (BAO) tower in southwestern Weld County in the DJB to investigate atmospheric mole fraction trends of methane and volatile organic compounds (VOCs). Elevated methane and propane mole fractions and low values (<1) in the ratio of i-pentane to n-pentane at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 29 publications
0
11
4
Order By: Relevance
“…A linear regression through this data for 2003-2012 yields a statistically insignificant trend of 1.25 ± 1.8 ppb. Oltmans et al (2021) found no significant trend in BAO CH 4 near Erie in the southwest portion of the Wattenberg from 2008 through mid-2016. We also found no significant trend for the DDJB AIRS enhancement from 2008 through 2016.…”
Section: Annual Statistics and Trends In Ch 4 And Ethanementioning
confidence: 71%
See 3 more Smart Citations
“…A linear regression through this data for 2003-2012 yields a statistically insignificant trend of 1.25 ± 1.8 ppb. Oltmans et al (2021) found no significant trend in BAO CH 4 near Erie in the southwest portion of the Wattenberg from 2008 through mid-2016. We also found no significant trend for the DDJB AIRS enhancement from 2008 through 2016.…”
Section: Annual Statistics and Trends In Ch 4 And Ethanementioning
confidence: 71%
“…Oltmans et al. (2021) found no significant trend in BAO CH 4 near Erie in the southwest portion of the Wattenberg from 2008 through mid‐2016. We also found no significant trend for the DDJB AIRS enhancement from 2008 through 2016.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…As we consider recent changes in emissions, however, changes in emissions per unit of production must also be considered. A recent study in the Northeastern Colorado Denver-Julesburg Basin showed little change in atmospheric hydrocarbons, including propane, in 2008-2016 despite a 7fold increase in oil production and a nearly tripling of natural gas production, suggesting a significant decrease in leak and/or venting rate per unit of production (Oltmans et al, 2021). While we cannot reliably estimate how propane emissions might have changed during this recent period, these two influences, combined together, could explain the observed temporary pause in the growth of atmospheric propane.…”
Section: Oandng Activitiesmentioning
confidence: 99%